If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 2(x + -3) = 30 Reorder the terms: X + 2(-3 + x) = 30 X + (-3 * 2 + x * 2) = 30 X + (-6 + 2x) = 30 Reorder the terms: -6 + X + 2x = 30 Solving -6 + X + 2x = 30 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6' to each side of the equation. -6 + X + 6 + 2x = 30 + 6 Reorder the terms: -6 + 6 + X + 2x = 30 + 6 Combine like terms: -6 + 6 = 0 0 + X + 2x = 30 + 6 X + 2x = 30 + 6 Combine like terms: 30 + 6 = 36 X + 2x = 36 Add '-2x' to each side of the equation. X + 2x + -2x = 36 + -2x Combine like terms: 2x + -2x = 0 X + 0 = 36 + -2x X = 36 + -2x Simplifying X = 36 + -2x
| 3x*12=3x*2 | | 6.99x+0.55=11.94 | | 5x^2+3y^2-8=0 | | X+0.07x=50 | | 3x+16=6x+198 | | 8x-4+6x+15=14x+11 | | 20/-d=13 | | 17+d=20 | | 14+4a=a+4-8 | | x+y(4)=120 | | 1+2n=-10+5-n+4n | | J-1.2(.4-.1j)=2.88 | | 0.4x=60 | | Bx+9=3y | | 5y+20=7x-56 | | x/5-7/4=x/10-1/20 | | -6n-5n=-16-7n | | 9/22=x/176 | | Ar=3r+14 | | 34=x/64 | | 63-f=52 | | K-8=5k-k-5 | | .2I+4(.3+.2I)=2.2 | | 14x+2=9x+20 | | 0.1x+0.2x=6 | | -(12-t)+(2t-4)= | | 17*v/v=7 | | 13/21=x/147 | | 6(x+9)=60 | | 1+2r-r=11+3r | | 12*c=156 | | 4y=-6+4x |